Strategic Capacity Planning and Production Line Efficiency In Kilogram Based Laundry Services: A Case Study of Dr Laundry - Fadhel Muhamad Zacky; Mita Afasli; Lusiana Lusiana (Jurnal Manajemen dan Profesional, 2026)
This case study examines capacity constraints at Dr Laundry, a small-scale service business established in 2021. Using a qualitative descriptive approach with field observations and interviews, the study reveals that despite a theoretical washing capacity of 975 kg/day and drying capacity of 325 kg/day, operational bottlenecks emerge when daily demand reaches 100 kg. The primary constraint does not arise from equipment limits or ironing speed (5–10 kg/hour/worker), but from process interruptions caused by overlapping cashier and washing responsibilities. Mitigation strategies including overtime extension, workforce allocation control, and load sequencing are evaluated. The findings demonstrate that task fragmentation and uncoordinated multi-role assignment degrade theoretical throughput in SME service lines, contributing to service operations management literature by highlighting that optimizing capacity does not necessarily require capital expansion, but rather targeted job redesign and process scheduling